História de vida em voz: narrativas sobre a arte de ensinar a encenar - Mendes, Adaíse Malvezzi [UNIFESP] (2017)
Voice is an essential means of communication for social interaction and a vital tool for some professional categories, among them, the classes of actors and teachers. The professional that works in the performing arts needs to deepen in the history of his character and build it, making his own body and his own voice recipients of a new person, to which he will give life on stage. The drama teacher, in turn, must pass on his artistic knowledge to his apprentices using his vocal abilities, in order to teach them how to act. In view of this, this research aims to analyze the teaching activity and the vocal aspects of the “teachers-actors”, who give theater classes, in three different working environments: non-governmental organization (NGO), private school and public school. The objective of this research is to understand the vocal use and working conditions, correlating them, as well to analyze the participants’ perceptions of a speech therapist's performance in the theater and in the performing arts classes. This work is justified by the very small number of studies carried out so far with this public, especially with those who consider the singularity of being on stage and the experience of teaching to act, interconnecting them with the use of their voice. Therefore, it is a qualitative study whose instruments for the production of data comprise the field diaries and the written production of narratives of life histories of the “teachers-actors”. It was possible to consider that the vocal use differs in the scenic performance, when compared to the exercise of teaching in performing arts. Working environments have similar conditions, both with regard to the physical aspects as the organizational. Concerning the speech therapist’s performance in the theater, only one participant considered that this professional works together with the actor in the construction of his character, going beyond technical aspects and vocal health.